Tinjauan penerimaan dan pelayanan customer di PT Mulya Sejahtera Technology Bandung - Jubaedah, Edah; Tianti, Ating Indah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the process of acceptance and customer service at PT Mulya Sejahtera Technology Bandung and how efforts are made to overcome factors or obstacles in favour and customer service at PT Mulya Sejahtera Technology Bandung. Qualitative descriptive analysis was used in this study using interview instruments and field observations. The results of this study involved receiving the goods are the warehouse/storeman, quality control, and supplier (vendor/supplier). They are supporting documents at the stage of receiving goods, namely Purchase Order (PO), Delivery Order (DO), Request Order Form (ROF), certificate and Packing List. In the implementation of receiving and servicing goods for customers/customers, it was found that there were problems with incomplete Authorized Release Certificate documents and unavailability of goods in the warehouse (0). Efforts to overcome these problems are: immediately submitting to the supplier so that the documents are completed, choosing a good supplier so that the papers sent are complete, constantly checking inventory so as not to run out of stock, accuracy in checking goods to be able to purchase goods properly. The efforts carried out will help the process of receiving and serving customers/customers well.